Application of Mineral Materials in Remediation of Heavy Metal Contaminated Soil - Liu CHANG; Shujuan DAI; Chunyun JIA; Zehao LIU; Zongqiang GONG (Kuangchan zonghe liyong, 2025)
With the increasingly serious pollution of heavy metals, the heavy metals in immobilized soil have become the focus of research in recent years, and mineral materials play an irreplaceable role in it. In this paper, the application and reaction mechanism of montmorillonite, sepiolite, zeolite, kaolin, attapulgite and other clay minerals as well as phosphate minerals and nano-mineral materials in the stabilization and remediation of heavy metal contaminated soil are summarized. The stabilization ability of clay minerals is related to mineral structure, which determines its ion-exchange ability. The stabilization effect of minerals with strong ion-exchange ability is more prominent. At the same time, clay minerals can also change the physical and chemical properties of soil, such as pH value, and reduce the activity of heavy metals in soil.The stabilization ability of phosphate minerals is positively correlated with its solubility, and the reaction mechanisms are mainly solution-precipitation, surface adsorption, ion exchange and induced adsorption. On the basis of retaining the properties of raw materials, nano-mineral materials also show some other characteristics due to their nano-size. In the future, further research can be conducted in the direction of material recovery and recycling, optimization of mineral modification methods, improvement of the stabilization effect of heavy metals and reduction of the stabilization period, in order to provide references for the research work of stabilization and remediation of heavy metals in soil.